THE CONVERSATIONAL IMPLICATURE USED BY THE MAIN CHARACTER IN I CARE A LOT MOVIE : A PRAGMATIC ANALYSIS - Fitriant, Nur Azizah; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
The aim of this research is to discover the maxims that the main characters in the film